Ethnobotanical investigation on medicinal plants used against human ailments in Erkowit and Sinkat areas, Eastern Sudan - MANAR ADAM; ABDEL AZIM AHMED; Ahmed Yagi; Sakina Yagi (Society for Indonesian Biodiversity, 2020)
Abstract. Adam M, Ahmed AA, Yagi A, Yagi S. 2020. Ethnobotanical investigation on medicinal plants used against human ailments in Erkowit and Sinkat areas, Eastern Sudan. Biodiversitas 21: 3255-3262. The present study provides ethnobotanical data for the traditionally used medicinal plants of Erkowit and Sinkat, Eastern Sudan. The survey data were collected from 53 traditional healers through a survey carried out in February-December 2018. Fifty-eight plant species represent 34 flowering families and one Parmeliaceae lichen that are used for therapeutic purposes in the selected area. The families of highest prevalence were Euphorbiaceae (8 species) followed by Leguminosae (7 species). To validate information on the use of plants,: Use Value (UV), Fidelity Level (FL), and Informants’ Consensus Factor (ICF) were applied. The most commonly used species was Adansonia digitata with a UV of 0.89. The majority of the informants agreed on the use of Oxalis anthelmintica to treat anemia and Psidium guajava in the treatment of tuberculosis and cough, with a very high FL (92% and 91% respectively). All informants agreed on the effectiveness of Withania somnifera in treating breast inflammation and cancer, with top ICF of 1. These medicinal plants play an important role in the available healthcare provision in the study area. This preliminary study should be further continued into scientific assessment of their therapeutic use and safety through different biological activity tests and toxicological properties.